Pengaruh Kualitas Produk, Harga, Lokasi, Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Buah Salak (Studi Kasus Pada RJ FRUITS Kecamatan Pronojiwo) - Rizal, Syarif Ali; Arifin, Rois; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze and describe the influence of product quality, price, location, electronic word of mouth on purchasing decisions for salak fruit (case study at RJ FRUITS, Pronojiwo District). The population in this research are consumers who have purchased at RJ FRUITS, Pronojiwo District. Determining the number of samples used the Malhotra formula and obtained results of 105 respondents. Data collection was carried out using a questionnaire. To solve the problem in this research using SPSS assistance with the analytical methods used in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F test, t test, coefficient of determination test (R2) . The research results show that product quality and location have a significant effect on purchasing decisions, while price and electronic word of mouth do not have a significant effect on purchasing decisions. Keywords: Purchasing Decisions, Product Quality, Price, Location, Electronic  Word Of Mouth.